A low-protein soybean-free diet improves carcass traits and meat quality and modulates the colonic microbiota in Daweizi pigs - Haohua Fu; Taoming Yang; Hengjia Ni; Hengjia Ni; Jing Li; Fenfen Liu; Jingbo Liu; Yulong Yin; Yulong Yin (Frontiers in Veterinary Science)
IntroductionSoybean meal is an excellent protein source and is widely used in pig feed. However, the Americas account for more than 80% of global soybean production, so European and Asia swine production largely depends on soybean imports. The use of safe and functional unconventional feed sources can effectively alleviate worldwide protein shortage problems.MethodsHere, we formulated a low-protein soybean-free diet (LPNS) for growing and fattening pigs using rice, potatoes, tea, and other unconventional feed sources. Thirty-six healthy Daweizi pigs (average body weight 23.60 ± 1.34 kg) were raised under the same conditions and randomly assigned to two dietary treatments: (1) Con group, corn-soybean base meal; (2) LPNS group. When the average weight of pigs in the group reached 85 kg, two pigs per pen were randomly selected and euthanized for collection of the colonic digesta and carcass traits and for meat quality determination.ResultsCompared with the corn-soybean based diet, the LPNS diet decreased the average daily gain (ADG) and feed conversion ratio (FCR) of Daweizi pigs but had a lower cost per kilogram of gain. In addition, the LPNS diet significantly increased leanness and decreased the fat-skin rate and bone rate of Daweizi pigs. The cooking loss of meat decreased, and unsaturated fatty acids such as C22:6 and n−3 PUFA significantly increased in the LPNS group. Moreover, the purine content in the meat substantially decreased with the LPNS diet. The 16S rDNA analysis revealed that the LPNS diet greatly modified the composition of the colonic microbiota community, with a decrease in the Firmicutes/Bacteroidetes ratio and an increase in the abundance of Lactobacillus spp.DiscussionThe use of functional herbs along with a low-protein diet helped to regulate fat and purine metabolism in fatty-type pigs. The LPNS diet formulated with unconventional-feed sources not only helps reduce the feed cost in swine production but also improves the carcass traits and meat quality of pigs, which is more suitable for small-scale pig farming.